Phenotypic and genotypic characterization of tomato genotypes for resistance to root-knot nematode, Meloidogyne incognita - Dhillon, Narpinderjeet; Kaur, Sukhjeet; Jindal, Salesh; Buttar, Harwinder (Phytoprotection, 2020)
Root-knot nematode is a major constraint to tomato cultivation in open and protected structures. Resistance sources need to be continuously identified for combating pathogens affecting the yield. In the present studies, forty-seven genotypes of tomato were evaluated phenotypically along with their genotypic characterization. On the basis of their phenotypic reaction, the genotypes were grouped into four categories viz.: resistant, moderately resistant, susceptible and highly susceptible. Of these genotypes, only five were found to be resistant while forty-two were rated from moderately resistant to highly susceptible. Multiplication of Meloidogyne incognita was greatly reduced (Rf < 1) in resistant genotypes as compared to susceptible genotypes. Root galling index was also very low in resistant genotypes. Using molecular markers, the presence of the Mi-1.2 resistance gene was also confirmed in five resistant genotypes (L-0272, NR-14, L-097, L-0275 and PNR-7). These resistant sources could become a source of germplasm in breeding programs for the development of resistant cultivars.